Political Clientelism as the Way of Survival of Radical Islamic Group Movement in Cianjur, West Java - Nur Kafid (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2018)
This study aims to analyze the existence and orientation shift of the radical Islamic group movement in the era of democratic decentralization, with the case study of Islamic Reformist Movement in Cianjur, West Java, therewith influencing factors. Based on the qualitative method, the data collected from various sources reveal that there is an orientation shift of radical Islamic group movement in the era of democratic decentralization; from 'Islamism' to 'premanism’. 'Islamism', that usually becomes the main issue, has now shifted to the domination of economic resources. This orientation shift is one of the ways for its survival. Patron-client political model of the New Order regime appears but in different forms; its characteristics and forms are also more fluid. Before and during the beginning of the Reformation Era, the orientation of radical Islamic group movement is more dominated by ideological motive such as the implementation of Islamic sharia, while during the era of democratic decentralization, its movement orientation shifts to economic pragmatism.